Data Resource Profile: Transforming Outcomes through Research in Cancer Healthcare in Victoria (TORCH-VIC) - Franchini, Fanny; Trapani, Karen; Soon, Jennifer; Gillett, Piers; Degeling, Koen; Daniels, Benjamin; Athan, Sophy; Pearson, Sallie-Anne; IJzerman, Maarten Joost (International Journal of Population Data Science, 2026)
Introduction The Transforming Outcomes through Research in Cancer Healthcare in Victoria (TORCH-VIC) is a comprehensive population-based cohort that links cancer diagnoses recorded in the Victorian Cancer Registry with administrative health data to capture the complete cancer journey from pre-diagnosis through long-term outcomes. Established in 2022, TORCH-VIC provides real-world evidence on healthcare utilisation, patterns of care, costs, and outcomes across the cancer continuum in Victoria, Australia. Methods TORCH-VIC comprises adults aged 18 years and over diagnosed with colorectal, lung, melanoma, prostate, breast cancer, and lymphoid leukaemia in Victoria, Australia, between January 2010 and December 2021, identified through the Victorian Cancer Registry. Cross-jurisdictional linkage of 11 data collections was performed by the Centre for Victorian Data Linkage for state datasets (hospital admissions, emergency presentations, radiotherapy, outpatient services, elective surgery, costs, and deaths) and the Australian Institute of Health and Welfare Data Linkage Unit for national datasets (Pharmaceutical Benefits Scheme (PBS), Medicare Benefits Schedule (MBS), National Death Index). Annual refresh ensures ongoing data currency. Results The dataset contains 222,332 unique individuals with 237,089 cancer diagnoses, stored securely in the Secure Unified Research Environment (SURE). Linkage rates exceed 98% for PBS and MBS data, with comprehensive inpatient hospital coverage (98.7%). The dataset captures over 250 million healthcare interactions across four phases: pre-diagnosis pathways, diagnosis, interventions, and outcomes. Data domains include socio-demographics, mortality, comorbidities, healthcare services, medicines, and costs. Mortality is comprehensively captured through linked state and national death registries (35.0% of cohort deceased). Loss to follow-up is minimal (1%), occurring primarily among individuals who emigrate or are ineligible for Medicare, with national datasets ensuring continued follow-up for those who relocate interstate within Australia. Conclusion TORCH-VIC enables research on cancer epidemiology, health service delivery, disparities in access, supportive care utilisation, survivorship, and healthcare costs. Applications span health services research, policy evaluation, and outcomes assessment. With ethics approvals secured, 2026 enhancements will add screening registers, immunisation data, and additional cancer types. Researchers interested in collaboration should contact the corresponding author to discuss projects within the study scope and ethics requirements.